Prehospital thrombolysis: lessons from Sweden and their application to the United Kingdom. Issue 6 (1st November 2002) - Benger, J R; Karlsten, R; Eriksson, B
Abstract : Objective: To study the successful implementation of paramedic administered prehospital thrombolysis in Sweden, and to consider the implications of this for the UK. Methods: A series of research visits were undertaken, including visits to Uppsala Hospital and dispatch centre, ambulance stations in several counties of Sweden and Dalarna County, which has one of the longest experiences of telemedicine supported prehospital thrombolysis in Europe. Data relating to prehospital thrombolysis, stages in successful implementation, and potential barriers to change were identified. Results: Two thirds of the hospitals in Sweden now have some form of prehospital thrombolysis. A nationally agreed and standardised training programme and the fact that many ambulance paramedics are also qualified nurses has facilitated successful introduction, but Sweden's low population density is also an important factor. Data from Dalarna County indicate that the median "pain to needle" time has been reduced by 45 minutes with a concurrent reduction in complications from 50% to 25% (p=0.018). Inhospital mortality has also reduced from 12% to 6%, but with the small numbers involved this improvement does not achieve statistical significance (p=0.36). Conclusion: If the outcome of acute myocardial infarction in the United Kingdom is to be improved, and National Service Framework targets met, then prehospital thrombolysis is an important development. Several technical solutions already exist, and a single bolus thrombolytic agent is now available, but the main barriers to full implementation are related to the establishment of an effective training programme and the organisational changes that will facilitate this new practice. High quality research is urgently needed to guide the implementation of prehospital thrombolysis in a clinically and cost effective way.